A fiducial continuum from confidence sets to empirical Bayes set estimates as the number of comparisons increases - Bickel, David R. (Université d'Ottawa | University of Ottawa, 2014)
Methods based on fiducial inference to hierarchical models that are formulated for set estimation propagate uncertainty to varying degrees. Some of the set estimates reduce to the usual confidence sets for a sufficiently low number of comparisons.